Are we meeting the standards set for endoscopy? Results of a large-scale prospective survey of endoscopic retrograde cholangio-pancreatograph practice. Issue 6 (4th December 2006) - Williams, Earl J; Taylor, Steve; Fairclough, Peter; Hamlyn, Adrian; Logan, Richard F; Martin, Derrick; Riley, Stuart A; Veitch, Peter; Wilkinson, Mark; Williamson, Paula J; Lombard, Martin
Abstract : Objective: To examine endoscopic retrograde cholangio-pancreatography (ERCP) services and training in the UK. Design: Prospective multicentre survey. Setting: Five regions of England. Participants: Hospitals with an ERCP unit. Outcome measures: Adherence to published guidelines, technical success rates, complications and mortality. Results: Organisation questionnaires were returned by 76 of 81 (94%) units. Personal questionnaires were returned by 190 of 213 (89%) ERCP endoscopists and 74 of 91 (81%) ERCP trainees, of whom 45 (61%) reported participation in <50 ERCPs per annum. In all, 66 of 81 (81%) units collected prospective data on 5264 ERCPs, over a mean period of 195 days. Oximetry was used by all units, blood pressure monitoring by 47 of 66 (71%) and ECG monitoring by 37 of 66 (56%) units; 1484 of 4521 (33%) patients were given >5 mg of midalozam. Prothrombin time was recorded in 4539 of 5264 (86%) procedures. Antibiotics were given in 1021 of 1412 (72%) cases, where indicated. Patients' American Society of Anesthesiology (ASA) scores were 3–5 in 670 of 5264 (12.7%) ERCPs, and 4932 of 5264 (94%) ERCPs were scheduled with therapeutic intent. In total, 140 of 182 (77%) trained endoscopists demonstrated a cannulation rate ⩾80%. The recorded cannulation rate among senior trainees (with an experience of >200 ERCPs) was 222/338 (66%). Completion of intended treatment was done in 3707 of 5264 (70.4%) ERCPs; 268 of 5264 (5.1%) procedures resulted in a complication. Procedure-related mortality was 21/5264 (0.4%). Mortality correlated with ASA score. Conclusion: Most ERCPs in the UK are performed on low-risk patients with therapeutic intent. Complication rates compare favourably with those reported internationally. However, quality suffers because there are too many trainees in too many low-volume ERCP centres.